Electron transport properties analysis of titanium dioxide dye-sensitized solar cells (TiO2-DSSCs) based natural dyes using electrochemical impedance spectroscopy concept: A review. (1st September 2020) - Omar, Azimah; Ali, Mohd Syukri; Abd Rahim, Nasrudin
Abstract: Energy crisis is the world major concern due to the rapid depletion of fossil fuel sources and its contribution to climate change. Among the solution in the clean and renewable energy sector is by employing one of the third-generation solar cell technologies known as a dye-sensitized solar cell (DSSC). The advantages of it include low cost, simple fabrication works, good performance at low illumination level and provide multi-color options of dyes either synthetic or natural dyes. Although the efficiency of DSSCs still low compared to the silicon or thin film-based solar cells, the performance of DSSCs can be improved by enhancing the dye part. The dye is one of the main components that influence the cell's performance whereby the implementation of the natural dyes is a promising way since natural sources are abundant, easy extraction processes and involve environmentally friendly energy concepts. However, the detailed mechanism of the charge transfer processes occurring inside the DSSC based natural dyes is still limited. Electrochemical impedance spectroscopy (EIS) analysis gave an enormous benefit in analyzing these mechanisms. It has been widely employed in the DSSC work to describe the relationship between the cell's performance, architectures and novel materials being used. This review aims to explore the electron transport properties that used the EIS concept and application. A brief introduction of EIS will be given, followed by a review of its application in the TiO2 -DSSCs based natural dyes. Finally, a brief discussion of future research directions and recommendations on this topic will be presented.